PERILAKU HIPERAKTIF SISWA DI SMP NEGERI 2 PINRANG - Sultan Sultan (IAIN PAREPARE, 2015)
This study aims to determine the hyperactive behavior of students in Junior High School 2 Pinrang. This type of research is qualitative research in the form of case studies on students who behave in a hyperactive. The technique used in data collection were interviews, observation, analysis and documentation. Data were analyzed with descriptive qualitative analysis. The results showed that the indicator hyperactive behavior of students are: 1) it is difficult to concentrate, 2) often does not do the work, 3) can not sit quietly, 4) often flicked friends, 5) impulsive, 6) often monopolize activities in social interaction. Impact hyperactive behavior of students are: 1) the decline in student achievement, 2) lack of harmony in social relationships with peers. Hyperactive behavior is influenced by the pattern of authoritarian parenting and unattended.